Helix Switching of a Key Active-Site Residue in the Cytochrome cbb3 Oxidases - HEMP, James; CHRISTIAN, Caroline; BARQUERA, Blanca; GENNIS, Robert B.; MARTíNEZ, Todd J. (Biochemistry (Easton), 2005)
In the respiratory chains of mitochondria and many aerobic prokaryotes, heme-copper oxidases are the terminal enzymes that couple the reduction of molecular oxygen to proton pumping, contributing to the protonmotive force. The cbb(3) oxidases belong to the superfamily of enzymes that includes all of the heme-copper oxidases. Sequence analysis indicates that the cbb(3) oxidases are missing an active-site tyrosine residue that is absolutely conserved in all other known heme-copper oxidases. In the other heme-copper oxidases, this tyrosine is known to be subject to an unusual post-translational modification and to play a critical role in the catalytic mechanism. The absence of this tyrosine in the cbb(3) oxidases raises the possibility that the cbb(3) oxidases utilize a different catalytic mechanism from that of the other members of the superfamily. Using homology modeling, quantum chemistry, and molecular dynamics, a model of the structure of subunit I of a cbb(3) oxidase (Vibrio cholerae) was constructed. The model predicts that a tyrosine residue structurally analogous to the active-site tyrosine in other oxidases is present in the cbb(3) oxidases but that the tyrosine originates from a different transmembrane helix within the protein. The predicted active-site tyrosine is conserved in the sequences of all of the known cbb(3) oxidases. Mutagenesis of the tyrosine to phenylalanine in the V. cholerae oxidase resulted in a fully assembled enzyme with nativelike structure but lacking catalytic activity. These findings strongly suggest that all of the heme-copper oxidases utilize the same catalytic mechanism and provide an unusual example in which a critical active-site residue originates from different places within the primary sequence for different members of the same superfamily.